NERVE GROWTH FACTOR NEUROPROTECTION OF ETHANOL-INDUCED NEURONAL DEATH IN RAT CEREBRAL CORTEX IS AGE-DEPENDENT - Mooney, Sandra M. (2007)
Organotypic cultures of rat cortex were used to test the hypotheses that nerve growth factor (NGF) is neuroprotective for immature cortical neurons and that ethanol abolishes this neuroprotection in a developmental stage-dependent manner. Samples were obtained on gestational day (G) 16 or postnatal day (P) 3 and cultured with ethanol (0 or 400 mg/dl) and NGF (0 or 30 ng/ml) for 72 hours. Dying neurons were identified as exhibiting terminal nick-end labeling, immunoreactivity for activated caspase 3, or condensed nuclear chromatin. Two cortical compartments were examined in fetal tissue; a superficial, cell-sparse marginal zone (MZ) and a cell-dense cortical plate (CP). At P3, the CP was subdivided into a cell-dense upper cortical plate (UCP) and a less densely packed lower cortical plate (LCP). Neuronal death in the MZ was affected by neither NGF nor ethanol at both ages. In the fetal CP, NGF did not affect the incidence of cell death, but ethanol increased it. Treatment with NGF caused an upregulation of the expression of Neg, a gene known to be affected by NGF and ethanol. NGF did not ameliorate the ethanol-induced death. In pups, ethanol increased the amount of death in the LCP. NGF did protect against this death. Neither ethanol nor NGF altered the incidence of cell death in the UCP. The laminar-dependent neuroprotection did not correlate with expression of NGF receptors or Neg. Thus, NGF can be protective against the neurotoxic effect of ethanol in the neonatal brain. This effect is site-selective and time-dependent and it targets post-migratory, differentiating neurons.